Strength and Permeation Characteristics of Zeolite-based Geopolymer Lightweight Concrete - Nader, Awaz S.; Hilal, Ameer A. (Iraqi Journal of Civil Engineering, 2025)
Geopolymer concrete is a material manufactured by polymerizing sources of aluminates and silicates like fly ash, metakaolin, slag, zeolite, etc. with an alkaline solution. A study has been undertaken to produce lightweight geopolymer concrete by using waste zeolite particles (zeolite molecular sieve) as aluminates and silicates source and at the same time as lightweight medium. In addition, others three geopolymer lightweight concrete mixes were produced by partially replacing the waste zeolite particles (25% of volume) with sources materials (fly ash type F, fly ash type C and waste zeolite powder. Moreover, the impact of this partially replacement on dry density, compressive strength and permeation characteristics of produced geopolymer lightweight mixes was studied. An alkaline solution of sodium silicate and sodium hydroxide was used in all the investigated mixes as an activator. From the findings, a geopolymer lightweight mix suitable for insulation purposes (density of 1610 kg/m3 and 28 days compressive strength of 5.1 MPa) was successfully produced using waste zeolite molecular sieve. It was found also that the lightweight zeolite particles were uniformly distributed through the produced mixes. Finally, it was found that replacement of 25% of volume of zeolite particles by fly ash (type C) helped in not only enhancing the compressive strength by about 13% but also reducing the water absorption by about 33%.